2019
DOI: 10.1016/j.celrep.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Mature Human White Adipocytes Cultured under Membranes Maintain Identity, Function, and Can Transdifferentiate into Brown-like Adipocytes

Abstract: Highlights d Mature adipocytes cultured as MAAC preserve cellular identity and function d Subcutaneous and visceral adipocytes can be cultured as MAAC d Adipocytes from lean and obese donors can be cultured d Human mature white adipocytes can transdifferentiate into brown-like adipocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 69 publications
(71 reference statements)
1
86
1
Order By: Relevance
“…They make it possible to observe regenerating preadipocytes and mesenchymal stem cells [40,41]. The first successful experiments on the cultivation of human adipose tissue explants were published by Smith in 1971, and recently Harms et al published an advancement of the ceiling culture method with mature human adipocytes [42,43]. In recent years, first tissue engineering methods for human adipose tissue have been developed [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…They make it possible to observe regenerating preadipocytes and mesenchymal stem cells [40,41]. The first successful experiments on the cultivation of human adipose tissue explants were published by Smith in 1971, and recently Harms et al published an advancement of the ceiling culture method with mature human adipocytes [42,43]. In recent years, first tissue engineering methods for human adipose tissue have been developed [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Others directly introduced primary adipocytes from mice into mesoscopic, perfused reservoirs 40 . In a recently introduced elegant approach, Harms et al cultured mature human white adipocytes in multiwell plates underneath membranes in a transwell format 41 . All of these innovative approaches, however, did not enable the generation of human white adipose tissue-like structures with in vivo-like physiology.…”
mentioning
confidence: 99%
“…Earlier studies have shown that the in vitro differentiation of pre adipocytes might be resulting in less mature adipocytes (Volz et al 2019). The maintenance and longterm culture of mature adipocytes has been shown to be successful by others (Harms et al 2019;Louis et al 2019). In the future this in vitro protocol could be carried out with mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%